Vpliv sten ob kontaktih z oblokom na izklopno zmogljivost nizkonapetostnega odklopnika - Bizjak, Martin (Informacije MIDEM, 2009)
The breaking capacity of low-voltage circuit breaker is closely related to thedevelopment of arc voltage and its magnizude during breaking of short-circuits current. The magnitude of let-through current shall be reduced and the joule integral minimized as well in order to achieve significant current-limiting effect of circuit breaker. Current limiting requires the magnitude of arc voltage to increase in the sufficirntly short time interval to the relatively stationary value above the certain critical voltage. Both of them are dependent on the movement of contact members during opening and on the elongation speed of arc column in the initial phase as wellas on the subdividing of arc in the arc chute. Numerical simulation of the variation of arc voltage and let-through current during the breaking time reveals the influencing quantilities of arc crucially affecting the current limiting action. The numerical procedure simulates the current and voltage waveforms normally recorded in oscillograms of breaking test shots, Some values necessary for the calculation were found in literature, others are used for simulation as variable parameters. The mutual combination of experimental and simulation results led us to the conclusion which physical effects, either movement of contacts or characteristics of materials (metallic and non-metallic) are dominant at break. By this way a significant influence of plastic material forming lateral walls around arching contacts onthe breaking capacity of circuit breaker under discussion was indicated qualitatively by comparing effects of two types of plastics.
Keywords: električni tok; materiali; napetost; oblok; odklopniki; vplivi